DIY stylus pen / Siti Rahmah Ramly ... [et al.] - Ramly, Siti Rahmah; Ibrahim, Zuzita; Ismail, Roziah; Tuan Mat, Tuan Arfah; Che Nazir, Nadzrul Iswandie; Abdul Rauf, Fadilah; Ngah, Nurul Najwa; Salman, Nurul Filza Nasuha (Universiti Teknologi MARA, Perak, 2020)
One of the characteristics of 21st Century Learning is student-centered learning. This feature is also suitable with the new norm environment as a result to Covid-19 transmission. In this situation, digital platforms such as Google Classroom (GC) become an intermediary medium between teachers and students. Through this platform, students are required to write answers from the questions given on paper and upload them to GC. However, during the Movement Control Order (MCO) season, many shops stopped operating, causing students to be unable to purchase stationery to complete their assigned tasks. Through this study a tool called DIY Stylus Pen has been produced to help students to continue to answer the questions given through their smartphones without having to write on paper. DIY Stylus Pen is produced using only pens that have run out of ink, cotton buds, and chrome wire. This method is more economical than stylus pens sold in the market. The development of this product has undergone 3 phases of improvement, starting with the use of chrome-plated aluminum paper in the first phase, then refinement by providing water containers and the third phase of aluminum paper has been replaced with chrome wire whose product quality is more durable. Feedback from students after use of DIY Stylus Pen, almost 90% of students stated that the use of this tool is easier and saves their time.